Gamification in higher education: Text mining approach - Loureiro, S. M. C. (2021)
Gamification is a growing trend in research (Caponetto, Earp, and Ott, 2014; Erenli, 2013; Kasurinen and Knutas, 2017) as well as in educational settings (Azmi, Ahmad, Iahad, and Yusof, 2017; Dicheva, Dichev, Agre, and Angelova, 2015). While a more common definition of gamification is still under evaluation throughout the research community, for this research we adopt the definition from (Deterding, Dixon, Khaled, and Nacke, 2011) - gamification is “the use of game design elements in non-game contexts”. Higher education is among one of those “non-game contexts” where the implementation and usage of gamification techniques, is evolving in an ascending trend and in various educational settings (e.g., Faghihi et al., 2014; Galbis-Córdova, Martí-Parreño, and Currás-Pérez, 2017). Different research methods have been used to explore not only the potential of gamification but also its pros & cons, regarding all areas of valuable application. In the present research, text mining techniques were used to perform an automated literature analysis, from 2011 to 2017, of gamification application in higher education settings.